Amide Synthesis by Nickel/Photoredox‐Catalyzed Direct Carbamoylation of (Hetero)Aryl Bromides. Issue 13 (25th February 2020) - Alandini, Nurtalya; Buzzetti, Luca; Favi, Gianfranco; Schulte, Tim; Candish, Lisa; Collins, Karl D.; Melchiorre, Paolo
Abstract: Herein, we report a one‐electron strategy for catalytic amide synthesis that enables the direct carbamoylation of (hetero)aryl bromides. This radical cross‐coupling approach, which is based on the combination of nickel and photoredox catalysis, proceeds at ambient temperature and uses readily available dihydropyridines as precursors of carbamoyl radicals. The method's mild reaction conditions make it tolerant of sensitive‐functional‐group‐containing substrates and allow the installation of an amide scaffold within biologically relevant heterocycles. In addition, we installed amide functionalities bearing electron‐poor and sterically hindered amine moieties, which would be difficult to prepare with classical dehydrative condensation methods. Abstract : Teaming up for amide synthesis : A catalytic method for amide synthesis is detailed that proceeds at ambient temperature and enables the direct carbamoylation of (hetero)aryl bromides. This method is based on the combination of nickel and photoredox catalysis and uses readily available dihydropyridines as precursors of carbamoyl radicals.